China’s returned migrant parents’ perspectives on how culture shapes their parenting in a culturally diverse community - Jinjin Lu (Humanities & Social Sciences Communications)
Abstract With technological and economic developments, several Chinese migrant families have returned to China from the West to China. Families with multilingual and multicultural backgrounds might experience more challenges in child-rearing than the locals. Drawing on a life-course perspective, we used a qualitative research method to investigate 18 Chinese returned migrant families with young children to enhance our understanding of the complex cultural and contextual issues in modern Chinese parenting. Findings reveal that individual experiences and family development are contextualised culturally and historically. The results highlight two contemporary Chinese socio-cultural factors, Tiger Mum and Lying Flat, which may influence Chinese parenting among the younger generation. Parenting is a complex, multidimensional, dynamic phenomenon. This study proposes that family migration experiences, family relationships, parents’ careers, and parenting styles should be considered to understand parental challenges better before resettlement.